Assessment of Quality of Life in Patients with Parkinson's Disease - Freddy Fernando Jumbo Salazar; Carlos Alejandro Troya Altamirano; Daniela Abigail Cobo Álvarez (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Foundation: parkinson's disease is a chronic progressive disorder of the nervous system that mainly affects motor coordination and movement control. Quality of life in patients with Parkinson's disease can vary widely depending on the severity of symptoms and the effectiveness of treatment. Objective: to analyze the quality of life of patients with Parkinson's disease in terms of factors: depression, cognitive functioning, age, sex, duration of the disease and education. Methods: descriptive and correlational, cross-sectional study. 40 people diagnosed with idiopathic Parkinson's disease and members of the Association of People with Disabilities were surveyed. The Mini Mental State Examination was used to assess cognitive functioning, the Parkinson's Disease Quality of Life Questionnaire to assess quality of life, and the Beck Depression Scale to assess emotional status. A non-parametric analysis was used to analyze the correlation, by performing several significance tests in correspondence with the distribution of the variables. The results were presented in quantities and percentages. Results: somatic problems, motor capacity, daily living activity, cognitive functioning and emotional state are among the most affected areas of life. Support from family members and communication with the social environment were the least impaired. A significant correlation was observed between depression and quality of life. Conclusions: the results suggest that early recognition and adequate treatment of depression can improve quality of life and reduce some of the somatic alterations of patients with Parkinson's disease.